TAMANHO DE PARCELA PARA ENSAIOS DE MILHO VERDE - Alves, Sueli Martins de Freitas; Seraphin, José Carlos; Seraphin, José Carlos; Zimmermann, Francisco José P.; Zimmermann, Francisco José P.; Silva, Ãlvaro Eleutério da; Silva, Ãlvaro Eleutério da (REVISTA DE AGRICULTURA, 2015)
TAMANHO DE PARCELA PARA ENSAIOS DE MILHO VERDE